Cyberloafing: A mapping of recent literature - Morales, Sergio; Morales, Oswaldo (Revista Colombiana de Ciencias Sociales, 2026)
At the beginning of the century, cyberloafing was defined as the personal use of the Internet during work hours. For two decades, various research analyzed its causes and effects. Nevertheless, in recent years, its study has increased significantly. In order to understand its development, this paper maps the literature (57 papers) published in the last 3 and a half years (2021-2024). The main finding is the existence of 7 thematic axes: 1) definition and conceptualization, 2) factors and antecedents, 3) effects and consequences, 4) theories, methods and techniques, 5) fields of study, 6) findings, limitations and recommendations, and 7) theoretical and practical implications. Unlike previous reviews, this one delves into underserved topics and highlights the importance of studying one of the most difficult organizational phenomena in recent years.